2020
DOI: 10.1021/acsnano.0c04748
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Direct-Write Skyrmion Nanolithography

Abstract: Magnetic skyrmions are stable spin textures with quasiparticle behavior and attract significant interest in fundamental and applied physics. The metastability of magnetic skyrmions at zero magnetic field is particularly important to enable, for instance, a skyrmion racetrack memory. Here, the results of the nucleation of stable skyrmions and formation of ordered skyrmion lattices by magnetic force microscopy in (Pt/CoFeSiB/W) n multilayers, exploiting the additive effect of the interfacial Dzyaloshinskii−Moriy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
(94 reference statements)
1
8
0
1
Order By: Relevance
“…We now discuss the possible mechanisms that lead to the observation of a zero-field skyrmion lattice in the FCGT nanoflakes. In previous works, zero-field Néel-type skyrmions have been stabilized by an exchange bias field ( 39 ), stray fields from MFM tips ( 40 , 41 ), and Joule heating ( 42 44 ) in multilayer ferromagnetic metal films. The exchange bias scenario can be eliminated because anomalous Hall measurements on zero-field skyrmion samples exhibit no measurable shift after either positive or negative field cooling (see fig.…”
Section: Resultsmentioning
confidence: 99%
“…We now discuss the possible mechanisms that lead to the observation of a zero-field skyrmion lattice in the FCGT nanoflakes. In previous works, zero-field Néel-type skyrmions have been stabilized by an exchange bias field ( 39 ), stray fields from MFM tips ( 40 , 41 ), and Joule heating ( 42 44 ) in multilayer ferromagnetic metal films. The exchange bias scenario can be eliminated because anomalous Hall measurements on zero-field skyrmion samples exhibit no measurable shift after either positive or negative field cooling (see fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, Zhang et al [31] showed that skyrmions were directly created by scanning the surface of a specimen by a magnetic force microscopy (MFM) tip with bias field. Using the same technique, Ognev et al [32] have demonstrated the creation of zero-bias-field skyrmion patterns with complex geometries, such as a toroid and an alphabet S. In a previous study [33], we demonstrated that even tiny surface pits with nanometer-scale dimensions fabricated by using a focused electron beam (surface-pit corral) are effective to confine stable skyrmion states. These unconventional techniques have the potential advantage of facilitating complex geometries that are difficult or even not feasible by conventional microfabrication techniques.…”
Section: Introductionmentioning
confidence: 80%
“…Микромагнитное моделирование проводилось в программном пакете MuMax3 [15], в котором решается уравнение Ландау−Лифшица−Гильберта [16] личина взаимодействия DMI изменялась в диапазоне 0−1.2 mJ/m 2 , что согласуется с экспериментальными данными [6,[17][18][19][20][21].…”
Section: исследуемые структуры и методика численного моделированияunclassified